2024
DOI: 10.1186/s12906-023-04318-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the protective effects of CS/TPP and CS/HPMCP nanoparticles containing berberine in ethanol-induced hepatotoxicity in rat

Maral Mahboubi Kancha,
Morteza Alizadeh,
Mohsen Mehrabi

Abstract: Background Alcoholic liver disease (ALD) is a globally critical condition with no available efficient treatments. Methods Herein, we generated chitosan (CS) nanoparticles cross-linked with two different agents, hydroxypropyl methylcellulose phthalate (HPMCP; termed as CS/HPMCP) and tripolyphosphate (TPP; termed as CS/TPP), and loaded them with berberine (BBr; referred to as CS/HPMCP/BBr and CS/TPP/BBr, respectively). Alongside the encapsulation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Other researchers have also reported encapsulation efficiency rates of around 75–80% for CS nanoparticles loaded with different drugs other than meropenem [ 54 , 55 ]. These values are consistent with the findings of our experiments.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Other researchers have also reported encapsulation efficiency rates of around 75–80% for CS nanoparticles loaded with different drugs other than meropenem [ 54 , 55 ]. These values are consistent with the findings of our experiments.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the characterization of the nanoparticles, other researchers have also used the same technique for the preparation of CS nanoparticles and have reported results consistent with our findings. For instance, Mahboubi Kancha et al have reported an average size of around 170–200 nm for CS nanoparticles [ 54 , 55 ]. The zeta potentials of our nanoparticles are also similar to those reported by Mahboubi Kancha et al as these researchers have reported a zeta potential of around 25–30 mV for their CS nanoparticles [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations